PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, SOLVABILITAS, KEPUTUSAN INVESTASI DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Arfan Arfan (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
This study aims to empirically examine the effect of profitability, company size, solvency investment decisions and debt policy on the value of the company in basic and chemical industry companies listed on the Indonesia Stock Exchange. This study uses a sample of basic and chemical industry companies listed on the Indonesia Stock Exchange during the period 2018 - 2020. Based on the purposive sampling method, the number of basic and chemical industry companies sampled in this study were 20 companies. Hypothesis testing uses panel data regression analysis using the EViews 10.0 program. The results showed that profitability had a positive effect on firm value. Meanwhile, company size, solvency, investment decision and debt policy have no effect on firm value.